Birds as Biodiversity Beacons: Identifying Conservation Priority Areas Through Multi-Dimensional Diversity in China - Fei Duan; Shuyi Zhu; Xiaoyun Shi; Xiaoli Shen; Sheng Li (Diversity, 2025)
Biodiversity conservation plays a pivotal role in achieving sustainable development and fostering harmonious coexistence between humans and nature. This study identifies avian conservation priority areas across China by analyzing multi-dimensional biodiversity, incorporating species diversity, functional diversity, and phylogenetic diversity. Through systematic conservation planning using Zonation version 4 software, we delineated priority areas across these diversity dimensions. Our results demonstrate a distinct south-to-north diversity gradient in China’s avifauna, with functional and phylogenetic diversity hotspots concentrated in Yunnan Province, the Hengduan Mountains, Hainan Island, Taiwan Island, and southeastern coastal regions. The identified priority conservation areas cover 14.6% of China’s terrestrial territory, protecting 89.8% of the country’s bird species—including 93.5% of endemic species and 88.9% of critically endangered species. Notably, existing nature reserves encompass merely 8.1% of these priority areas, revealing substantial conservation gaps within the current protection framework. Building upon China’s 3C Zoning Framework (Cities and farms, Shared landscapes, and Large wild areas), we propose zone-specific conservation strategies, with particular emphasis on strengthening protected area networks in the eastern coastal regions and the middle-lower Yangtze River basin, where urbanization pressures are most acute. These findings highlight the critical importance of incorporating multi-dimensional diversity in conservation planning and offer novel perspectives for optimizing China’s protected area system.